The Influence of Using the Picture and Picture Method in Enhancing Students' Speaking Ability - Ariesta, Maharani; Shalihah, Siti; Maksum, Ali (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This research aims to determine the influence of utilizing the Picture and Picture method in enhancing the speaking skills of 7th-grade students at MTsN 3 Kota Tangerang (State Islamic Junior High School 3 Tangerang City). This study employed a quantitative approach with a quasi-experimental design, involving two classes: an experimental class taught using the Picture and Picture method and a control class taught using conventional methods. Data were collected through a pre-test and post-test, then analyzed using the t-test. The research findings indicate a significant increase in the post-test results of students in the experimental class compared to the control class. The average score of students in the experimental class increased from 54.84 to 72.81 after the treatment, whereas the control class only increased from 56.37 to 58.10. Thus, it can be concluded that the Picture and Picture method is effective in enhancing Arabic speaking skills.